2022
DOI: 10.3389/fphar.2022.793087
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Protects Against Titanium Particle-Induced Osteolysis by Attenuating Osteoclast Formation and Function by Inhibiting NF-κB and MAPK Signaling

Abstract: Bone homeostasis only exists when the physical function of osteoblast and osteoclast stays in the balance between bone formation and resorption. Bone resorption occurs when the two processes are uncoupled, shifting the balance in favour of bone resorption. Excessive activation of osteoclasts leads to a range of osteolytic bone diseases including osteoporosis, aseptic prosthesis loosening, rheumatoid arthritis, and osteoarthritis. Receptor activator of nuclear factor kappa-B ligand (RANKL) and its downstream si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Exposure of macrophages to titanium particles released into the surrounding tissue after implant placement can significantly increase ROS production, inducing NF-κB activation and local inflammation, leading to decreased osteoblast function and increased osteoclast activity. The inflammatory process is closely linked to oxidative stress, which is caused by an imbalance of oxidant formation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of macrophages to titanium particles released into the surrounding tissue after implant placement can significantly increase ROS production, inducing NF-κB activation and local inflammation, leading to decreased osteoblast function and increased osteoclast activity. The inflammatory process is closely linked to oxidative stress, which is caused by an imbalance of oxidant formation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclast activation and local inflammatory response play a nonnegligible role in titanium particle-induced osteolysis. Titanium particles can cause monocytes/macrophages to trigger the release of proinflammatory factors, initiate an inflammatory cascade response, release osteoclasts, promote osteoclast recruitment, migration, and differentiation, and ultimately activate bone resorption, leading to osteolysis [ 38 ]. Panicker et al [ 39 ] reported that DA inhibited NLRP3 inflammasome activation via D1R, thereby regulating inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The process of bone remodeling on titanium implant surfaces involves interactions among osteoclast precursor cells, osteoclasts, mesenchymal stem cells, and osteoblasts. Only by maintaining the balance of bone resorption and bone formation can the stability of bone tissue be maintained . Therefore, the effect of the implant surface on osteogenesis, its regulation of osteoclastogenic differentiation, and the interaction between them needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Only by maintaining the balance of bone resorption and bone formation can the stability of bone tissue be maintained. 27 Therefore, the effect of the implant surface on osteogenesis, its regulation of osteoclastogenic differentiation, and the interaction between them needs to be further explored. In this study, we simulated the morphology of the osteon and applied a GO coating to the substrate and then verified the regulation of osteogenic and osteoclastogenic differentiation by the composite modified material in single and indirect cocultures.…”
Section: Discussionmentioning
confidence: 99%